Finding the roots?

Algebra Level 3

3 2 x 2 7 x + 3 = 4 x 2 x 6 \large 3^{2x^{2} - 7x + 3} = 4^{x^{2} - x - 6}

There are two roots to the equation above. One of the roots is 3 3 and the other root is of the form

A + B ( log C log D ) E log F log G \frac {A + B \left(\frac {\log C}{\log D}\right)}{E - \frac {\log F}{\log G}}

where A A , B B , C C , D D , E E , F F , and G G are positive integers with C C , D D , and G G being primes. Input your answer as the minimum value of A + B + C + D + E + F + G A + B + C + D + E + F + G .


The answer is 19.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Aug 11, 2020

3 2 x 2 7 x + 3 = 4 x 2 x 6 3 ( 2 x 1 ) ( x 3 ) = 4 ( x + 2 ) ( x 3 ) ( 2 x 1 ) ( x 3 ) log 3 = ( x + 2 ) ( x 3 ) log 4 \begin{aligned} 3^{2x^2-7x+3} & = 4^{x^2-x-6} \\ 3^{(2x-1)(x-3)} & = 4^{(x+2)(x-3)} \\ (2x-1)(x-3)\log 3 & = (x+2)(x-3) \log 4 \end{aligned}

Therefore, x = 3 x=3 is a root. And the other root is given by:

( 2 x 1 ) log 3 = ( x + 2 ) log 4 = 2 ( x + 2 ) log 2 2 x log 3 2 x log 2 = log 3 + 4 log 2 x = log 3 + 4 log 2 2 log 3 2 log 2 = 1 + 4 log 2 log 3 2 log 4 log 3 \begin{aligned} (2x-1)\log 3 & = (x+2) \log 4 \\ & = 2(x+2)\log 2 \\ 2x\log 3 - 2x \log 2 & = \log 3 + 4 \log 2 \\ \implies x & = \frac {\log 3 + 4 \log 2}{2\log 3 - 2 \log 2} \\ & = \frac {1 + 4 \cdot \frac {\log 2}{\log 3}}{2 - \frac {\log 4}{\log 3}} \end{aligned}

Therefore, A + B + C + D + E + F + G = 1 + 4 + 2 + 3 + 2 + 4 + 3 = 19 A+B+C+D+E+F+G = 1+4+2+3+2+4+3 = \boxed{19}

@Barry Leung , you should key \log C log C \log C and not log C l o g C log C so that the log is not italic and there is a space between log and C.

You should also mention A A to G G are integers. Because 4 log 2 log 3 = 4 3 log 8 log 3 4 \cdot \dfrac {\log 2}{\log 3} = \frac 43 \cdot \dfrac {\log 8}{\log 3} . You should also fixed some of the integers because log 4 log 3 = log 16 log 9 = log 64 log 27 = \dfrac {\log 4}{\log 3} = \dfrac {\log 16}{\log 9} = \dfrac {\log 64}{\log 27} = \cdots infinitely many of them. So when it comes final answer it should be as simple as possible.

Chew-Seong Cheong - 10 months ago

3 2 x 2 7 x + 3 = 4 x 2 x 6 2 x 2 7 x + 3 = ( x 2 x 6 ) log 3 4 ( 2 log 3 4 ) x 2 ( 7 log 3 4 ) x + 3 + 6 log 3 4 = 0 ( 2 k ) x 2 ( 7 k ) x + ( 3 + 6 k ) = 0 \begin{aligned}3^{2x^2-7x+3}&=4^{x^2-x-6}\\\iff 2x^2-7x+3&=(x^2-x-6)\log_34\\\iff (2-\log_34)x^2-(7-\log_34)x+3+6\log_34&=0\\\iff (2-k)x^2-(7-k)x+(3+6k)&=0\end{aligned}

Where k : = log 3 4 k:=\log_34 .

Knowing x = 3 x=3 is a root, we can use polynomial long division (dividing by x 3 x-3 ) to see that this holds when ( x 3 ) [ ( 2 k ) x ( 1 + 2 k ) ] = 0 (x-3)[(2-k)x-(1+2k)]=0 .

The roots are then x = 3 x=3 or x = 1 + 2 k 2 k = 1 + 2 log 4 log 3 2 log 4 log 3 x=\dfrac{1+2k}{2-k}=\dfrac{1+2\frac{\log 4}{\log 3}}{2-\frac{\log 4}{\log 3}} , since k = log 3 4 = log 4 log 3 k=\log_34=\dfrac{\log 4}{\log 3} (where the logarithm has the base of any positive number not equal to 1 1 ).

The answer is then 1 + 2 + 4 + 3 + 2 + 4 + 3 = 19 1+2+4+3+2+4+3=\color{#20A900}{\boxed{19}} .

One may also apply the quadratic formula here to get the same result, however this is tricky and errors may occur. If doing so, I would suggest making a substitution like I did for k k to reduce the chance of making mistakes.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...